Physiological consequences of Aldolase C deficiency during lactation. - James A Votava; Jing Fan; Brian W Parks (PLoS ONE, 2024)
The lactating mammary gland strongly induces de novo lipogenesis (DNL) to support the synthesis of fatty acids, triglycerides, and cholesterol found within milk. In monogastric species, glucose is a major substrate utilized for DNL within the lactating mammary gland and must be efficiently taken up and processed to supply cytosolic acetyl-CoA for DNL. Along with the enzymes of the DNL pathway, the glycolytic enzyme, Aldolase C (Aldoc), is transcriptionally upregulated and is highly expressed during lactation in the mammary gland, suggesting a role for Aldoc in lactation. Aldoc is also a transcriptional target of the sterol regulatory element binding proteins 1 and 2 (Srebp1 and Srebp2), which transcriptionally regulate enzymes within the DNL pathway and has recently been shown to regulate plasma cholesterol and triglycerides. Here, we investigate the role of Aldoc in lactation, by utilizing a whole-body Aldoc knockout mouse. Our results demonstrate that Aldoc has a significant impact on lactation, whereby pups nursing from Aldoc-/- dams have reduced body weight. Biochemical analysis of milk identified that milk from Aldoc-/- dams have significantly higher galactose, lower lactose, and cholesterol content. Mass spectrometry analysis of milk lipids from Aldoc-/- dams revealed significantly lower quantities of medium and long chain fatty acid containing triglycerides, which has direct implications on lactation as these are the predominant triglycerides synthesized from glucose in human mammary gland. Overall, our results provide functional evidence for the contribution of Aldoc in mammary gland lactose and lipid synthesis during lactation.